Associations between perceptions of odors and dryness and children's asthma and allergies: A cross-sectional study of home environment in Baotou. (September 2016) - Bu, Zhongming; Wang, Lifang; Weschler, Louise B.; Li, Baizhan; Sundell, Jan; Zhang, Yinping
Abstract: We analyzed perceptions of odors and dryness and their associations with asthma and allergic symptoms in 1–8 year-old children in Baotou, China. In this cross-sectional study, parents returned 4801 completed questionnaires. Odors reported frequently or sometimes were stuffy odor, 45.2%; unpleasant odor, 33.8%; pungent odor, 9.7%; moldy odor, 9.2%; tobacco smoke odor, 33.2%; dry air, 72.4% and humid air, 22.5%.Perceptions of all odors and of dry air (POD)were strongly associated with the risk of children's asthma and allergies but the perception of humid air was not. Dwelling owners reported significantly less odor perception than renters. Significant risk factors for POD were family history of asthma or allergies, living near a main road or highway, evidence of moisture related problems and never exposing bedding to sunshine. A higher proportion of women and allergic persons reported POD. The perception of dryness positively correlated with the use of humidifiers. We conclude that perception of odors and/or dryness can be proxies for indoor pollution, and as such, indicators of increased risk for children's asthma and allergic symptoms. Reducing moisture related signs and keeping good sanitary habits, both of which can be at least partially accomplished by ventilation, are likely effective strategies for addressing odors and dryness problems in residences. Graphical abstract: Highlights: Perceived odor and dryness as related to children's asthma and allergies were studied. Household factors as related to perceptions of odors and dryness were analyzed. Perceptions of odors and dry air were associated with children's asthma and allergies. Perception of dry air is often a proxy for indoor air pollution. Specific agents causing perceptions of odors and dryness need to be identified.